Effectiveness of opicapone and switching from entacapone in fluctuating Parkinson disease. (22nd May 2018) - Ferreira, Joaquim J.; Lees, Andrew J.; Poewe, Werner; Rascol, Olivier; Rocha, José-Francisco; Keller, Birgit; Soares-da-Silva, Patricio
Abstract : Objective: To evaluate the effectiveness of opicapone as add-on to levodopa and the effects of switching from entacapone over 1 year of treatment in patients with fluctuating Parkinson disease. Methods: After completion of a placebo- and entacapone-controlled double-blind study of opicapone (5, 25, or 50 mg), 495 patients continued to a 1-year extension phase in which patients were treated with opicapone. Patients began with once-daily opicapone 25 mg for 1 week, followed by individually tailored levodopa and/or opicapone dose adjustments. The primary efficacy variable was the change from baseline in absolute "off" time based on patient diaries. Other outcomes included proportion of responders, scale-based assessments, and standard safety assessments. Results: One year of treatment with opicapone reduced "off" time by a half-hour (33.8 minutes) vs the open-label baseline and >2 hours (126.9 minutes) vs the double-blind baseline. Whereas patients who were originally treated with opicapone 50 mg in the double-blind phase maintained their efficacy, switching treatments led to further decreases in "off" time (−64.9, −39.3, −27.5, and −23.0 minutes for switching from placebo, entacapone, and opicapone 5 and 25 mg, respectively). Dyskinesia was the most frequently reported adverse event (14.5%) and was managed by adjustment of dopaminergic therapy. No new safety concerns were observed with long-term opicapone administration. Conclusion: Long-term use of opicapone provided sustained efficacy over 1 year. Switching from entacapone to opicapone led to enhanced efficacy under the conditions of the study. Classification of evidence: This study provides Class III evidence that for patients with Parkinson disease and end-of-dose motor fluctuations, long-term use (52 weeks) of opicapone is well tolerated and reduces "off" time.